Patterns of claims and determinants of claim rejections in Kuwait's National Health Insurance for Retirees (AFYA): a comprehensive analysis - Alibrahim, Abdullah I.; Kelendar, Hisham; Alhenaidi, Abdulaziz (Frontiers in Public Health, 2025)
IntroductionHealth insurance claim rejections can impose significant administrative and financial burdens, yet data from emerging national programs are limited. Kuwait's AFYA program, launched in 2016 for retirees, provides a valuable opportunity to study rejection patterns and identify the demographic and service-level factors that influence denial rates in a rapidly evolving high-income context.MethodsThis retrospective study analyzed 4.44 million AFYA claims from 2016 to 2023. Key variables included beneficiary characteristics (age group, sex), provider type, service category (dental, medical, pharmaceutical), claimed amount, and claim year. Logistic regression was employed to determine predictors of claim rejection, controlling for all the above factors. Sensitivity analyses excluded the top 1% of claimed amounts to check for robustness.ResultsThe overall rejection rate was 3.85%, lower than reported rates in some established systems. Younger retirees (under 40) had 1.82 times higher odds of claim denial than the reference group (56–60), and female beneficiaries had 1.21 times higher odds than males. Dental services were associated with a 2.28-fold increase in rejections relative to pharmaceutical claims. Laboratory claims, though relatively rare, showed exceptionally high rejection proportions. Rejection rates gradually declined over time, from 4.15% in 2017 to 3.42% by 2023. The most frequent reasons for denial involved uncovered services and insufficient clinical justification.DiscussionThese findings underscore the critical role of clear coverage definitions, consistent coding, and effective administrative oversight in minimizing denials. Younger retirees, female beneficiaries, and certain service types (dental, laboratory) emerged as particularly vulnerable to rejections, indicating the need for targeted policy refinements. Notably, the downward trend in rejections suggests that AFYA has capacity for adaptive improvements over time.ConclusionBy revealing pivotal factors that drive or mitigate claim rejections, this analysis offers practical guidance for policymakers and healthcare administrators. Standardized electronic forms, provider feedback loops and tighter coverage definitions could trim residual denials without restricting access. AFYA's experience offers transferable lessons for high-income countries seeking to expand private-sector purchasing while containing cost.